CERTIFIED VERSUS UNCERTIFIED ELECTRONIC SIGNATURES: LEGAL CONSEQUENCES AND BEST PRACTICES IN INDONESIA - Farhan Hamka Ilyasa; Ariawan Gunadi (Transpublika Publisher, 2024)
This article examines the legality and validity of electronic signatures in Indonesia, especially for crucial documents such as the Power of Attorney and Letters of Indemnity, in the light of digital transformation. In this study, a normative legal research method, more popularly known as doctrinal research, was employed, where an in-depth analysis of the legislative texts and available legal materials is needed to construct sound legal reasoning. Approach: The paper combines a conceptual analysis of legal principles with a statutory approach that analyzes whether there is harmony within the various legislative provisions. Various statutes and regulations in Indonesia are critically analyzed, including the Law on Electronic Information and Transactions, Government Regulation concerning the Execution of Electronic Systems and Transactions, and the Minister of Communication and Informatics Regulation on Electronic Certification. The discussion should be centered on what legal provisions must be in place for the acceptance of electronic signatures certified and those not certified. It, therefore, sets out the legal implications of the use of electronic signatures and gives comprehensive recommendations of the best practices as a means of ensuring legal certainty and legality in their implementation in Indonesia. The Journal is intended to assist businesses and lawyers to pass through those issues with ease. To this end, this journal will consider in great detail the legal framework for electronic signatures.